The mouse X chromosome is enriched for sex-biased genes not subject to selection by meiotic sex chromosome inactivation - Khil, Pavel P; Smirnova, Natalya A; Romanienko, Peter J; Camerini-Otero, R Daniel (Nature genetics, 2004)
Sex chromosomes are subject to sex-specific selective evolutionary forces 1 , 2 . One model predicts that genes with sex-biased expression should be enriched on the X chromosome 2 , 3 , 4 , 5 . In agreement with Rice's hypothesis 3 , spermatogonial genes are over-represented on the X chromosome of mice 6 and sex- and reproduction-related genes are over-represented on the human X chromosome 7 , 8 . Male-biased genes are under-represented on the X chromosome in worms and flies 9 , 10 , 11 , however. Here we show that mouse spermatogenesis genes are relatively under-represented on the X chromosome and female-biased genes are enriched on it. We used Spo11 −/− mice blocked in spermatogenesis early in meiosis 12 to evaluate the temporal pattern of gene expression in sperm development. Genes expressed before the Spo11 block are enriched on the X chromosome, whereas those expressed later in spermatogenesis are depleted. Inactivation of the X chromosome in male meiosis may be a universal driving force for X-chromosome demasculinization.